ChemInform Abstract: Progress in Piezo‐Phototronic‐Effect‐Enhanced Light‐Emitting Diodes and Pressure Imaging. Issue 15 (24th March 2016) - Pan, Caofeng; Chen, Mengxiao; Yu, Ruomeng; Yang, Qing; Hu, Youfan; Zhang, Yan; Wang, Zhong Lin
Abstract: Review: [86 refs.